A performance queer na dupla encenação do filme The Watermelon Woman // The queer performance in the double staging of the film The Watermelon Woman - Xavier de Lima, Marília; Cunha de Lyra, Maria Bernadette; Carlos Magno, Maria Ignês (Contemporanea, 2018)
The Watermelon Woman (1996), Cheryl Dunye, é um modelo híbrido de ficção/documentário. A dupla encenação vai da busca de uma atriz negra do cinema mudo ao cotidiano da própria diretora/personagem. Uma associação entre forma e conteúdo permite igualar-se à representação da personagem o deslocamento dos gêneros cinematográficos, tornando o filme uma performance queer, em que a história sobre a vida da mulher-melancia e a realidade de Cheryl se mesclam, dando visibilidade à mulher negra e lésbica./The Watermelon Woman (1996), Cheryl Dunye, is a hybrid movie that is between fiction and documentary model. The double performance goes from the search of a black actress of the silent cinema period to the daily life of the director / character. An association between form and content allows the representation of the character to be equated with the displacement of the cinematographic genres, making the film a queer performance, in which the story about the life of the watermelon woman and the reality of Cheryl merge, giving visibility to the woman black and lesbian.